Cover Feature: Three‐Dimensional Hierarchical Framework Loaded with Lithiophilic Nanorod Arrays for High‐Performance Lithium‐Metal Anodes (ChemElectroChem 20/2020). Issue 20 (23rd September 2020) - Qi, Yanyuan; Lin, Lin; Jian, Zelang; Qin, Kaiyan; Tan, Yuxuan; Zou, Yujie; Chen, Wen; Li, Fujun
Abstract : The Cover Feature illustrates the Li stripping/plating behaviors on the 3D lithiophilic nanorod arrays structure. The nanorod arrays supply a large number of Li deposition sites. The abundant channels along nanorods provide sufficient buffer space for Li deposition and Li + dissolution, and thus suppress the volume change and promote non‐dendritic Li plating. As a result, the Li composite electrode with the 3D hierarchical host exhibits excellent electrochemical properties. More information can be found in the Article by W. Chen et al .